MANAJEMEN KONFLIK DALAM ORGANISASI SISWA INTRA SEKOLAH DI SMA PLUS AL-HASAN - Adela Yanuar Ismi; Haris Nurdiansah; Ulfatul Hasanah; Siti Lutfiah (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2022)
In the dynamics of an organization, the occurrence of a conflict is indeed something that is very prone to occur. Given how the competition is very tight, it creates a conflict that we cannot avoid. Then conflict management is used in terms of managing and overcoming and tackling well the existence of a conflict within the organization. The focus of this research is how is conflict management in an intra-school student organization that occurred at SMA PLUS AL – HASAN? with the aim of knowing how to manage conflict in an organization, the importance of conflict management in an organization and conflict resolution strategies in an organization. This research uses a descriptive qualitative research method which in collecting data uses a technique of observation, interviews and documentation. This research has produced several things related to how conflict management in organizations, the importance of conflict management in organizations and how to strategy a conflict resolution in an organization.